Combination of Ruxolitinib and Eculizumab for Treatment of Severe SARS-CoV-2-Related Acute Respiratory Distress Syndrome: A Controlled Study - Giudice, Valentina; Pagliano, Pasquale; Vatrella, Alessandro; Masullo, Alfonso; Poto, Sergio; Polverino, Benedetto Maria; Gammaldi, Renato; Maglio, Angelantonio; Sellitto, Carmine; Vitale, Carolina; Serio, Bianca; Cuffa, Bianca; et al. (Frontiers in Pharmacology, 2020)
To date, there are no specific therapeutic strategy for treatment of COVID-19. Based on the hypothesis that complement and coagulation cascades are activated by viral infection, and might trigger an acute respiratory distress syndrome (ARDS), we report clinical outcomes of 17 consecutive cases of SARS-CoV-2-related ARDS treated (N = 7) with the novel combination of ruxolitinib, a JAK1/2 inhibitor, 10 mg/twice daily for 14 days and eculizumab, an anti-C5a complement monoclonal antibody, 900 mg IV/weekly for a maximum of three weeks, or with standard of care (N = 10). Patients treated with the combination showed significant improvements in respiratory symptoms and radiographic pulmonary lesions and decrease in circulating D-dimer levels compared to the best available therapy group. Our results support the use of combined ruxolitinib and eculizumab for treatment of severe SARS-CoV-2-related ARDS by simultaneously turning off abnormal innate and adaptive immune responses.